BELALANG SEBAGAI IDE PERANCANGAN SEPATU FASHION WANITA MODEL DERBY WEDGE - Anisa Aulia; Wawan Budi Setyawan (Politeknik ATK Yogyakarta, 2018)
Grasshopper is an icon from Gunungkidul area which is a tourist destination today and has been adapted to batik motifs as well as various beautiful accessories. To introduce grasshoppers to the wider world, shoes are a new medium of introduction that can be used. Leather base material on the upper part gives the impression of luxury in building image of dressing. The robustness of the wood outsole and the uniqueness of engraving on the outsole present a different aesthetic value than the fashion shoes in general. The authors applied the leather and wood products in the form of women's fashion shoes with grasshoppers as design ideas that will give the impression of feminine, luxurious, and unique. In the making of this final work, a derby wedge model of women's fashion shoes was raised as a design idea. Data collection methods were by observing, documenting, distributing questionnaires, interviewing and conducting literature studies related to the material raised. The sampling technique used was non probability sampling by purposive sampling. The process of designing and manufacturing of products that was done in this self- supporting activity consists of: existing product, brainstorming, image board, stylation, user study, design sketch, movement study, idea sketch, and product making. To produce the same product with the design that made the necessary trials many times and takes a long time.